Designing Games for Cultural Heritage: Integrating Process, Material Culture and Intangible Heritage. Issue 2 (June 2015) - Goins, Elizabeth; Phelps, Andrew; Egert, Christopher
This paper reviews a number of cultural heritage games that have been developed by faculty at the Center for Media, Arts, Games, Interaction & Creativity (MAGIC) at the Rochester Institute of Technology. Fundamental to designing engaging cultural heritage games is that of integrating material culture, social history and intangible cultural heritage. There is not much existing guidance on how to successfully create engaging heritage games and in this paper we outline some of the main issues and conclude with a few ideas that might help move the field forward.